An investigation in the level of local community education on sustainable tourism development: The case of Uraman Takht in Iran: The local community sustainable tourism - Movahed, Ali; Jafarpour Ghalehteimouri, Kamran; Hashemi, Ehasan (Turizam, 2024)
Tourism is known as one of the most dynamic economic activities and it plays an important role in sustainable local development. Uraman Takht is a collection of five villages that is part of the city of Sarvabad in Kurdistan Province and is one of the typical tourist areas. This study evaluates the level of education of the people of Uraman in relation to local sustainable tourism development. The aim of this study is to identify the effectiveness of environmental education on sustainable tourism development in the local community. The findings indicate that sustainable tourism with an average indicator (2.64), because the obtained average is considered below average, (3) indicates a low level of education in tourism in Uraman. The second indicator is the level of knowledge and awareness of people about sustainable tourism with an average (3.22) because the average obtained is considered to be above average (3) indicates the level of knowledge and awareness about tourism. The last indicator is tourism economic, social and environmental changes, with an average (3.78) the average obtained is considered too moderate and close to (3) then the changes showing in various dimensions of tourism.